Molecular detection of the pathogen of Apis mellifera (Hymenoptera: Apidae) in honey in Indonesia - IGM RAKA ALPIN ADITYA; HARI PURWANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Aditya IGMRA, Purwanto H. 2023. Molecular detection of the pathogen of Apis mellifera (Hymenoptera: Apidae) in honey in Indonesia. Biodiversitas 24: 2612-2622. Apis honey bees play a major role in global crop pollination. The honey bee population faces various threats, one being entomopathogens, responsible for 13% of honey bees' declining population cases. Some major pathogens are Nosema sp., Melissococcus plutonius, and Paenibacillus larvae. Data on the prevalence of these pathogens is not available in Indonesia. Therefore, this study aimed to detect entomopathogen in Java, Bali, and Sumatra honey. We extracted 30 honey samples from Java, Bali, and Sumatra in this study. DNA from honey amplified by conventional Polymerase Chain Reaction (PCR) to detect Nosema apis, Nosema ceranae, M. plutonius, and P. larvae. Amplicons were sequenced to confirm the species of pathogens detected. Results showed that N. ceranae has a 20% prevalence, found in Java and Bali; M. plutonius was, for the first time, found in Indonesia and only in Java, with a 3.33% prevalence. In comparison, this study didn't find N. apis and P. larvae. Environmental factors were studied for their correlation with the incidence of pathogens. From several factors, only precipitation significantly correlates with the occurrence of N. ceranae and M. plutonius, while other factors do not. This research concludes that honey can be used as source of DNA for pathogens detection and monitoring in a certain area globally.